The influence of socio-economic status and parental education level on motivation to continue studying at higher education - Sitti Marlina; Musdalifah; Nurul Fajriah Yahya; Sumarni Abdul Rahim; Syamsul Bahri (International Journal of Advances in Educational Research, 2025)
This research aims to analyze the influence of socio-economic status and parental education level on the motivation of Class XII students at Yaspib Bontolempangan High School to continue their studies at university. In this study, socio-economic status was measured based on parents' employment and income, while parents' education level was seen from the last level of education completed. The research method used is a quantitative method by collecting data through direct observation at schools, distributing questionnaires to students, and documentation. Data analysis was carried out using multiple linear regression to determine the relationship between these variables and students' motivation to continue their education to the next level. The research results indicate that although socio-economic status and the level of parents' education have an impact on students' motivation to continue their studies in several other studies, this research found the opposite. It shows that there is no significant influence of socio-economic status and parents' education level on students' motivation to pursue higher education, either partially or in relation to each variable. This study suggests that other factors may have a greater influence on the decision of 12th-grade students at Yaspib Bontolempangan High School to continue their studies at a university.